Effect of applying Total Quality Management in improving the performance of Al-Waqf of Albr Societies in Saudi Arabia: a theoretical framework for "Deming's Model = أثر تطبيق إدارة الجودة الشاملة في تحسين أداء أوقاف جمعيات البر في المملكة العربية السعودية: إطارا نظريا لتطبيق نموزذج "ديمنج" - Ali Saad, Alwidhi Zakaria; Mohd Noor, Azman; Ashurov, Sharofiddin (EuroMid Academy of Business & Technology (EMABT), 2020)
This study aims to examine the effect of applying Total Quality Management (TQM) on improving the performance of the management of Al-Waqf of Alba societies in the Kingdom of Saudi Arabia through the optimal application of Deming's 14 Points on quality management. The research problem lies in the weakness of the outputs of Alba societies in terms of quality and productivity due to the lack of monitoring and control over those in charge of managing these charities. The researcher is going to use descriptive qualitative, interviews, and the case study approach to achieve the research's objectives. After an intensive review of the literature, this study confirmed the research gap and lack of empirical studies in implementing the TQM in charity organizations precisely in Saudi Arabia.